Zebrafish as a Model for Germ Cell Regeneration - Cao, Zigang; Yang, Qifen; Luo, Lingfei (Frontiers in Cell and Developmental Biology, 2021)
Germ cell acts as a link between transfer of genetic information and process of species evolution. Defects or malformations of germ cells can lead to infertility or tumors. Germ cell regeneration is one of the effective ways to treat the infertility. Therefore, it is of great scientific and clinical interests to dissect the cellular and molecular mechanisms underlying germ cell regeneration. Progress have already been achieved in germ cell regeneration using model organisms for decades. However, key open issues regarding the underpinning mechanisms still remain poorly understood. Zebrafish is well known for its powerful regenerative capacity to regenerate various tissues and organs. Recently, advances in genomics, genetics, microscopy, and single cell technologies have made zebrafish an attractive model to study germ cell development and regeneration. Here we review recent technologies for the study of germ cell regeneration in zebrafish, highlight the potential of germline stem cells (GSCs) in the contribution to reproductive system regeneration, and discuss the nanos. Wnt signaling and germ cell-specific factors involved in the regulation of germ cell regeneration.